Analysis of Student Errors in Solving Mathematical Story Problems Based on Newman's Theory in View of Student Learning Styles - Ulfa, Siti Maria; Zuhri, Zainullah (Universitas Negeri Surabaya, 2023)
This study aims to describe the types of errors experienced by students in solving mathematical word problems based on Newman's theory in terms of the learning styles of junior high school students. This type of research is a qualitative descriptive research. The subjects of this study were class VIII students at SMP Negeri 3 Pasuruan, Pasuruan Regency, for the 2022/2023 academic year. The subjects of this study were 2 students with visual learning styles, 2 students with auditory learning styles, and 2 students with kinesthetic learning styles. Data collection techniques in this study were observation, giving learning style questionnaires, social arithmetic story questions, interviews and documentation. The data obtained was tested for its validity by technical triangulation. The results of this study are 1) Students with a visual learning style tend to make all mistakes except reading and understanding problems, 2) Students with an auditory learning style tend to make all mistakes except reading mistakes and, 3) Students with a kinesthetic learning style also tend to make all errors except read errors.